(untitled) (Research, Society and Development, 2025)
Mancozeb is a broad-spectrum fungicide widely used in agriculture; however, its poor water solubility limits its operational efficiency and increases environmental impact. Cyclodextrins, particularly 2-hydroxypropyl-β-cyclodextrin (HP-β-CD), have emerged as promising carriers capable of enhancing the solubility, stability, and agronomic performance of poorly soluble active ingredients. This article presents a technological prospecting study covering scientific publications and patents, focusing on inclusion complex formation, analytical evidence of molecular interactions, and potential applications in agrochemical formulations. The findings reveal a significant gap in the literature regarding the mancozeb/HP-β-CD inclusion complex, highlighting the innovative potential of this strategy for developing more efficient and environmentally friendly formulations.